O impacto da ocupação de fundos de vale em áreas urbanas. Caso: Córrego do Gregório - São Carlos (SP) - Borges, Juliana Queiroz (Universidade Federal de São Carlos, 2006)
The present work proposes a debate that interrelates three areas of knowledge urbanization, urban drainage and social segregation and has the main purpose to analyze the occupation of river marginal areas in urban places as the main cause for temporary social segregation. It also proposes a discussion about this impact caused by the occurrence of floods. The research strategy used is the study of an exploratory single case made in the city of São Carlos-SP, more specifically in the central area belonging to the Gregório River Basin, characterized for having solid occupation with great commercial activity. Besides theoretical basis, we have done a research on how many floods have occurred during 1995 and 2005, in the works fulfilled by the City Government, and also interviews with five groups of social actors. The results obtained with the conclusion of the work had, in its greatest parts, a social and educational value, involving consciousness of the necessity of environment preservation; of the eventually irreversible damages caused by the occupation of environmentally fragile areas, such as floodable fertile valleys. The research has also been detached as a relevant instrument to subsidize new debates and researches. As far as the social actors are included, we have verified that the most damaged ones in the cases of floods, in the unity of analysis, were the businessmen, and 70% of these consider themselves victims of temporary social segregation. This way, it was possible to confirm the main hypothesis of the work: temporary social segregation can be considered a consequence of inadequate occupation of river marginal areas in urban places, and this may involve lots of situations, including the ones that do not refer to the condition of poverty and misery.
Keywords: Planejamento urbano; Drenagem urbana; Fundos de vale; Inundações; Exclusão social; Urbanização; Urbanization; River marginal areas; Urban drainage; Floods and temporary social segregation; ENGENHARIAS